Potensi Ekstrak Terpurifikasi Daun Umbi Bit (Beta vulgaris) sebagai Antioksidan dan Penetapan Kadar Flavonoid Totanya - Diah Pratimasari; Dian Puspitasari; Noor Anisa (Jurnal Farmasi Indonesia, 2023)
The ethanol extract of beetroot leaves contains high levels of phenolic and flavonoid compounds, making it potentially beneficial as an antioxidant. However, the ethanol extract of beetroot leaves has a disadvantage as it is still mixed with other components that are not necessary, limiting its formulation development. In relation to this, the purpose of this research is to eliminate unwanted compounds as antioxidants and to observe the impact of purification on the antioxidant activity and total flavonoid content of the extract. The production of purified extract involves fractionating the suspension of beetroot leaf extract using solvents with different polarities, namely n-hexane and ethyl acetate, in sequence. Antioxidant activity tests are conducted on Ethanol Extract of Beetroot Leaves (EEDUB), Purified Extract of Beetroot Leaves (ETDUB), and quercetin as a positive control. Antioxidant activity is assessed using 2,2-Diphenyl-1-Picrylhydrazyl (DPPH). The total flavonoid content of EEDUB and ETDUB is determined with a spectrophotometer using AlCl3. The antioxidant activity of EEDUB is indicated by an IC50 value of 157.87 µg/mL, while ETDUB has an IC50 value of 129.60 µg/mL. The total flavonoid content of EEDUB is 2.82% ± 0.85 QE, and for ETDUB, it is 2.90% ± 1.16 QE. The research results show that ETDUB has a higher flavonoid content and antioxidant activity compared to EEDUB. This also indicates that the purification process of the beetroot leaf extract has not reached its maximum effectiveness.